Antidotal effect of sodium dimercaptosuccinate against acute poisoning by the monosodium salt of 2-dimethylamino-1,3-bisthiosulfo-propane - Chen Zhi-kang; Zheng Guo-tong; Chen Xing-yan; Lin Dan (Acta Pharmacologica Sinica; Vol 6, No 3 (September 1985): Acta Pharmacologica Sinica, 2016)
The pesticide monosodium salt of 2-dimethylamino-1, 3-bisthiosulfo-propane(SCD) is a nereisotoxin derivative. In mice,the prophylactic effect of sodium dimercaptosuccinate(DMS) was better than the therapeutic effect, the large dose better than the small dose,and iv better than ip or ig,ip and ig had almost the same effect.The antidotal effect of DMS were both prophylactic and therapeutic in SCD-poisoned rabbits, as DMS decreased the mortality and prolonged the survival time. When DMSand SCD were mixed, the IR characteristic absorption band of the SH groups of DMS at 2520 cm(-1) disappeared.